Akcja polskiej placówki dyplomatycznej na Węgrzech wobec „reakcyjnych” organizacji polonijnych (1946–1950) - Sylburska, Aleksandra (Acta Universitatis Lodziensis. Folia Historica, 2014)
Polish diaspora’s organisations functioned in Hungary since the 19th century. Their main goal was to integrate Polish society, mainly to support those whose material situation was difficult and to mantain the Polish national identity among the members of the diaspora. In 19th century there were around 40 thousands members of Polish diaspora, in the interwar period – 30 thousands. The number increased dramatically during the II World War, when 140 thousands of refugees crossed Polish-Hungarian border. In a post-war period the repatriation started and in 1949 only 2500 Polish citizens stayed in Hungary. After 1945 few diaspora’s organisations were founded and from the beginning they were controlled by Polish diplomatic post. In 1946–1950 the pressure which were exerted on organisations were increasing every year. Diplomats, according to the recommendations of Polish Foreign Affaires Office, interefered in the activity of organisations, e.g. they had impact on the election of their managements. Eventually they led to elimination of diaspora’s organisations and in 1950 none of them functioned in Hungary.